2015
DOI: 10.15306/mvpjms/2015/v2i2/78304
|View full text |Cite
|
Sign up to set email alerts
|

Study of Diagnostic Importance of Adenosine Deaminase (ADA) Level in Pleural Effusions

Abstract: Introduction: Pleural effusion is the abnormal accumulation of fluid in the pleural space. TB is the most common cause of pleural effusion worldwide (30-60%). The pleural fluid activity of adenosine deaminase (ADA) is one of the best, providing reliable basis for a treatment decision, particularly in excluding the diagnosis of tuberculosis, due to its high sensitivity1. Aims and Objectives: To assess the importance of adenosine deaminase(ADA) level in the diagnosis of pleural effusion. To assess Adenosine Deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a similar study by Sachin Kate et al, which included 75 patients, the sensitivity/specificity/PPV/NPV of pleural fluid ADA in diagnosing TB pleural effusion was 93.3%/90%/93%/90%. 24 Another study by A. Trajman et al, who evaluated 132 patients (95 Tubercular) the sensitivity and specificity of pleural fluid ADA was 91% and 93% respectively. 4 In a meta-analysis by Goto et al, who analyzed nearly 40 studies from Cochrane and Medline database concluded that pleural fluid ADA was an efficient diagnostic tool in diagnosing TB pleural effusions and had sensitivity of 47.1-100% with specificity of 50-100%.…”
Section: Discussionmentioning
confidence: 96%
“…In a similar study by Sachin Kate et al, which included 75 patients, the sensitivity/specificity/PPV/NPV of pleural fluid ADA in diagnosing TB pleural effusion was 93.3%/90%/93%/90%. 24 Another study by A. Trajman et al, who evaluated 132 patients (95 Tubercular) the sensitivity and specificity of pleural fluid ADA was 91% and 93% respectively. 4 In a meta-analysis by Goto et al, who analyzed nearly 40 studies from Cochrane and Medline database concluded that pleural fluid ADA was an efficient diagnostic tool in diagnosing TB pleural effusions and had sensitivity of 47.1-100% with specificity of 50-100%.…”
Section: Discussionmentioning
confidence: 96%